The development of perceptual-cognitive skills in youth volleyball players - De Waelle, S.; Warlop, G.; Lenoir, M.; Bennett, S. J.; Deconink, F. J. A. (Journal of Sports Sciences, 2021)
In many sports, elite players outperform novices on tests for perceptual-cognitive skills, such as anticipation, decision-making and pattern recall. However, the developmental trajectory of these perceptual-cognitive skills has received limited attention. Therefore, this study examined the development of anticipation, decision-making and pattern recall in 202 female volleyball players aged between 7 and 26 years old. Participants were categorized into six age groups: U9, U11, U13, U15, U17 and Seniors. Using a video-based occlusion protocol, we assessed participants` ability to predict pass direction, decide the most optimal attack zone, or recall the opponents` defence positions. The results demonstrated that U17 and adult players had superior accuracy and shorter response times than younger players on all three tests. Notably, U9 players performed worse than older players on all tests. Binomial distributions showed that decision-making was above chance for U17 players and adults, whereas anticipation was above chance for almost all players. Our findings indicate that age-related improvements of perceptual-cognitive skills are evident at 11 years old. However, decision-making seems to develop considerably later than anticipation and pattern recall, suggesting different developmental trajectories for the different perceptual-cognitive skills. Longitudinal research regarding the development of perceptual-cognitive skills and their underlying mechanisms is warranted, as this could have important implications for talent detection and development.